2003
DOI: 10.1094/cm-2003-1112-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Double-cropping Winter Wheat and Soybean Improves Net Returns in the Eastern Great Plains

Abstract: In the eastern Great Plains, winter wheat (Triticum aestivum L.) and different soybean [Glycine max(L.) Merr.] maturity groups (MG) are grown in various cropping systems to diversify crop production. A 10‐year field study was conducted in southeastern Kansas to evaluate effects of multi‐cropping systems on grain yield and net economic returns. Cropping systems evaluated were: (i) annual double‐cropping of wheat and soybean (MG IV); (ii) four 2‐year rotations of wheat‐soybean double‐cropped followed by full‐sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The maximum economic grain yields for grain sorghum occurred at the N level of 90 kg N ha −1 . Double‐cropping soybean or grain sorghum after wheat increases cropping intensity and results in extensive use of fixed resources, improved cash flow, and increased net returns (Kelley, 2003). In this study, grain sorghum in the double‐cropped soybean system gave the greatest economic net return.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum economic grain yields for grain sorghum occurred at the N level of 90 kg N ha −1 . Double‐cropping soybean or grain sorghum after wheat increases cropping intensity and results in extensive use of fixed resources, improved cash flow, and increased net returns (Kelley, 2003). In this study, grain sorghum in the double‐cropped soybean system gave the greatest economic net return.…”
Section: Discussionmentioning
confidence: 99%
“…Although the economics of dual crop systems in the South are generally favorable (Kyei‐Boahen and Zhang, 2006), results have been mixed in the Great Plains. For instance, Kelley (2003) found that over a 10‐yr period in Kansas, wheat ( Triticum aestivum L.)–soybean double‐cropping systems provided significantly greater net returns than a conventional 2‐yr wheat–soybean rotation. Conversely, Moomaw and Powell (1990) found that relay‐ and double‐crop wheat–soybean systems did not give as high a return as did growing each as a monocrop.…”
mentioning
confidence: 99%
“…In semiarid regions with low precipitation, fallow periods are important to recharge soil water and minimize risks of cash crop failure due to drought stress (Nielsen & Vigil, 2010; Nielsen, Vigil, & Hansen, 2016), but it also promotes greater risks of soil degradation (e.g., soil erosion and decreased organic matter) and N loss. When water is not a limiting factor, double‐cropping (i.e., harvest of two crops from the same land unit in a calendar year) has the advantage to increase the efficiency of land and water use as well as farm profitability (Kelley, 2003). According to Borchers, Truex‐Powell, and Nickerson (2014), soybean [ Glycine max (L.) Merr] is the most common double‐crop (53% of total acres), and is planted immediately after winter wheat harvest.…”
Section: Introductionmentioning
confidence: 99%